The role of parenting stress on parenting self-efficacy and parental burnout among Turkish parents: a moderated mediation model - Yahya AKTU (BMC Psychology)
Abstract Objective Parental burnout is a significant problem that negatively effects parent-child interaction, parenting skills, and child well-being. Research has identified parenting stress as one of the leading factors in parent burnout. Although crucial connections have been explained between parenting stress and parental burnout, not much is known about how parenting self-efficacy operates in these relationships. This study aims to investigate the roles of parenting self-efficacy and number of children in the relationship between parenting stress and parental burnout. Methods The participants consist of a total of 456 parents (M age = 35.64 ± 9.28, Range = 25–65 years). The data were collected using a personal information form, the Parenting Stress Scale, the Parental Burnout Scale and the Parenting Self-Efficacy Scale. Relationships among variables were examined using Pearson’s correlation, while moderated mediation analysis was carried out using Hayes’s bootstrapping. Results The correlation analyses reveal a negative relationship between parenting self-efficacy and parenting stress, between parenting self-efficacy and parental burnout, and between parenting self-efficacy and number of children, while a positive significant relationship was found between parenting stress and parental burnout. The mediation analyses show parenting self-efficacy to mediate the correlation between parenting stress and parental burnout. The mediating effect of parenting self-efficacy is also moderated by number of children. Conclusions This study provides empirical evidence for the effect of parenting stress and parenting self-efficacy on parental burnout, with fewer children in the household alleviating parental burnout.